Performance of Novel TWO-CAP (Thin-Walled Open Channel Angular Pressing) Method on AA5083 - KENTLİ, AYKUT (KOREAN INST METALS MATERIALS, 2021)
Newly developed severe plastic deformation (SPD) method TWO-CAP was applied to AA5083 to increase its mechanical properties. The method was developed to obtain the structural beams which have a thin-walled open-cross section area in high strength to weight ratio. During the TWO-CAP process, the annealed U-profile specimens will be pressed along the specifically designed die channel with the help of the hydraulic press machine. After the expansion and narrowing processes, the specimen leaves the die with initial dimensions at the end of each pass. Therefore, the material gains strength, hardness, and toughness while the microstructure of the material was improved as a result of the SPD. In order to determine the effect of the TWO-CAP on the mechanical properties of the material, the hardness and tension tests were carried out on the all passed specimens. Also, the characteristic investigations were performed on the specimens by using optical microscopy, SEM-EDS, and XRD analyses. Graphic Abstract
Keywords: Mechanical tests; Microstructural analysis; SPD; Thin-walled beam; SEM-EDS; XRD; SEVERE PLASTIC-DEFORMATION; MECHANICAL-PROPERTIES; MICROSTRUCTURE EVOLUTION; STEEL; SIZE